Synthesis, Characterization and Optimization of Oleyl Oleate Wax Ester Using Ionic Liquid Catalysts - Naowara Al-Arafi; Nadia Salih; Jumat Salimon (Indonesian Journal of Chemistry, 2021)
In this work, the synthesis of oleyl oleate wax ester using Brønsted acidic ionic liquid catalysts was carried out. Confirmation of oleyl oleate molecular structure has been performed using FTIR, NMR, and ESI-MS spectroscopies. The ability of ionic liquid catalysts for catalyzing the esterification reaction of oleic acid and oleyl alcohol to produce oleyl oleate was optimized. The ionic liquid catalyst ([NMP][CH3SO3]) was found to be the best catalyst for the esterification reaction of oleic acid and oleyl alcohol compared with the other acidic ionic liquids studied. The optimal reaction conditions were determined at a reaction time of 8 h; oleic acid to oleyl alcohol mole ratio of 1:1; ([NMP][CH3SO3]) with 9.9 wt.%; and reaction temperature of 90 °C. Under these conditions, the percentage yield of oleyl oleate wax ester was 86%.